2018
DOI: 10.1042/bsr20180628
|View full text |Cite
|
Sign up to set email alerts
|

Development of a biodegradable antifibrotic local drug delivery system for glaucoma microstents

Abstract: To prevent implant failure due to fibrosis is a major objective in glaucoma research. The present study investigated the antifibrotic effects of paclitaxel (PTX), caffeic acid phenethyl ester (CAPE), and pirfenidone (PFD) coated microstent test specimens in a rat model. Test specimens based on a biodegradable blend of poly(4-hydroxybutyrate) biopolymer and atactic poly(3-hydroxybutyrate) (at.P(3HB)) were manufactured, equipped with local drug delivery (LDD) coatings, and implanted in the subcutaneous white fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The analysis of the drug release from the sintered PLA@PF implants was performed in vitro in physiological conditions (PBS, 37 °C). This experiment demonstrated that the complete release of PF from PLA@PF implants was prolonged to 80 h, following the initial more rapid release of approximately 50% of the drug during first 20 h. This release time was much longer than the period reported for the different types of PF-loaded ocular lenses (up to 12 h) [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 78%
“…The analysis of the drug release from the sintered PLA@PF implants was performed in vitro in physiological conditions (PBS, 37 °C). This experiment demonstrated that the complete release of PF from PLA@PF implants was prolonged to 80 h, following the initial more rapid release of approximately 50% of the drug during first 20 h. This release time was much longer than the period reported for the different types of PF-loaded ocular lenses (up to 12 h) [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 78%
“…A total of 16.12 µg PFD was released within a time frame of 10 h in vitro. Disregardless of the relatively fast drug release the PFD coating effectively reduces capsule thickness and the growth of the capsule throughout the 6 months observation period [5].…”
Section: Discussionmentioning
confidence: 99%
“…A valve mechanism is used for controlled drainage of aqueous humour, a drug eluting-coating focusses on the prevention of fibrosis and an injector device is used for minimally invasive ab interno implantation into suprachoroidal or alternatively subconjunctival space ( Fig. 1) [5][6][7]. PFD loading of the drug eluting coating was chosen according to Jung et al who implanted conventional Ahmed FP8 GDD (New World Medical Inc., USA) into New Zealand White rabbits adjunctive with an intraoperative injection of 200 µg PFD in a 200 µl solution incorporated with 1 mg ml -1 PFD [4].…”
Section: Microstent Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the cardiovascular system, stents are being researched in ophthalmologic (glaucoma drainage) [4,5], otorhinolaryngologic (Eustachian tube, treatment of chronic otitis media) [6], as well as gynecologic (Fallopian tube), see Figure 2, and gastroenterologic (pancreas) application. The latter being applied in the context of endoscopic pancreatic necrosectomy [7], see Figure 3.…”
Section: Current and Future Workmentioning
confidence: 99%